2014
DOI: 10.1080/14786419.2014.927873
|View full text |Cite
|
Sign up to set email alerts
|

Two new xanthones from the pericarp ofGarcinia mangostana

Abstract: Two new xanthones, designated garcimangosxanthone F (1) and garcimangosxanthone G (2), were isolated from the EtOAc-soluble fraction of ethanolic extract from the pericarp of Garcinia mangostana. Their structures were established as 1,6,7-trihydroxy-5-(3-methylbut-2-enyl)-8-(3-hydroxy-3-methylbutyl)-6',6'-dimethylpyrano[2',3':3,2]xanthone and 1,6,7-trihydroxy-5-(3-methylbut-2-enyl)-8-(3-hydroxy-3-methylbutyl)-6',6'-dimethyl-4',5'-dihydropyrano[2',3':3,2]xanthone, respectively, on the basis of their 1D, 2D NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Previous studies have also reported the presence of various types of xanthones in different parts of G. mangostana , including the pericarp. Some of the identified xanthones derived from pericarp are mangostinone, α-mangostin, β-mangostin, γ-mangostin, gartanin, garcinone E, 1,5-dihydroxy-2-(3-methylbut-2-enyl)-3- methoxyxanthone, 1,7-dihydroxy-2-(3-methylbut-2-enyl)-3-methoxyxanthone [ 46 ], 8-hydroxycudraxanthone G, mangostingone, cudraxanthone G, 8-deoxygartanin, garcimangosone B, garcinone D, garcinone E, gartanin, 1-isomangostin, mangostinone, smeathxanthone A, tovophyllin A, mangostanaxanthones I, mangostanaxanthones II, 9-hydroxycalabaxanthone, parvifolixanthone C, rubraxanthone [ 47 ], 1,3,7-trihydroxy-2-(3-methyl-2-butenyl)-8-(3-hydroxy-3-methylbutyl)-xanthone, 1,3,8-trihydroxy-2-(3-methyl-2-butenyl)-4-(3-hydroxy-3-methylbutanoyl)-xanthone, garcinones C, garcinones D, gartanin, xanthone I [ 48 ], garcimangosxanthone F (1), garcimangosxanthone G [ 49 ], and mangostanate [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported the presence of various types of xanthones in different parts of G. mangostana , including the pericarp. Some of the identified xanthones derived from pericarp are mangostinone, α-mangostin, β-mangostin, γ-mangostin, gartanin, garcinone E, 1,5-dihydroxy-2-(3-methylbut-2-enyl)-3- methoxyxanthone, 1,7-dihydroxy-2-(3-methylbut-2-enyl)-3-methoxyxanthone [ 46 ], 8-hydroxycudraxanthone G, mangostingone, cudraxanthone G, 8-deoxygartanin, garcimangosone B, garcinone D, garcinone E, gartanin, 1-isomangostin, mangostinone, smeathxanthone A, tovophyllin A, mangostanaxanthones I, mangostanaxanthones II, 9-hydroxycalabaxanthone, parvifolixanthone C, rubraxanthone [ 47 ], 1,3,7-trihydroxy-2-(3-methyl-2-butenyl)-8-(3-hydroxy-3-methylbutyl)-xanthone, 1,3,8-trihydroxy-2-(3-methyl-2-butenyl)-4-(3-hydroxy-3-methylbutanoyl)-xanthone, garcinones C, garcinones D, gartanin, xanthone I [ 48 ], garcimangosxanthone F (1), garcimangosxanthone G [ 49 ], and mangostanate [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taro starch can be used as an industrial raw material. It could improve the stability of Pickering emulsion ( Zhang et al, 2020 ), and it could be used for the treatment of wastewater generated during printing and dyeing ( Zhou et al, 2018 ) and as an enhancer of starch film ( Dai et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For simpler solvent partitioning, only a single solvent, e.g. ethyl acetate [ 51 ] or chloroform [ 52 ], is employed for liquid-liquid extraction with the initial alcohol fraction.…”
Section: Introductionmentioning
confidence: 99%